2010
DOI: 10.1145/1816038.1816000
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of thread-level parallelism in desktop applications

Abstract: As the effective limits of frequency and instruction level parallelism have been reached, the strategy of microprocessor vendors has changed to increase the number of processing cores on a single chip each generation. The implicit expectation is that software developers will write their applications with concurrency in mind to take advantage of this sudden change in direction. In this study we analyze whether software developers for laptop/desktop machines have followed the recent hardware trends by creating s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…However, they also showed that desktop applications leveraged TLP very sparingly. This result was echoed 10 years later by Blake et al [1] with a similar study of TLP of contemporary software and hardware, when multi-core had become the norm rather than the exception in home and office desktops. They reported that 2-3 cores were more than adequate for almost all but a few domain specific applications like Video Authoring.…”
Section: B Early Studies On Tlpmentioning
confidence: 82%
See 4 more Smart Citations
“…However, they also showed that desktop applications leveraged TLP very sparingly. This result was echoed 10 years later by Blake et al [1] with a similar study of TLP of contemporary software and hardware, when multi-core had become the norm rather than the exception in home and office desktops. They reported that 2-3 cores were more than adequate for almost all but a few domain specific applications like Video Authoring.…”
Section: B Early Studies On Tlpmentioning
confidence: 82%
“…High GPU utilization also indicates that some of the parallelism is already offloaded from the CPU to the GPU. All these factors, and the history of the slow pace of exploiting parallelism in desktop environments [1], suggests that having many powerful cores is likely to be overprovisioning.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations